Attitude towards Statistics among students of Dentistry - Díaz-Reissner, Clarisse Virginia (2018)
Objective: To analyze the attitude towards statistics in undergraduate students of a Paraguayan university´s Dentistry faculty enrolled in Investigation Methodology and Biostatistics´courses in 2015, was the objective of the investigation. Methods: A quasi- experimental study was conducted. The SATS-36 questionnaire (Survey of Attitude Toward Statistics) was used to measure the attitude toward statistics before and after the course. Results: The sample was conformed by 43 students, 83.72% was female, with 19 ± 3.14 year-old age average, 48.96% graduated from the Humanistic Bachelor`s degree and 48.84% wanted to obtain a "Very Good" rating. Based on the scores obtained, the "difficulty" (p=0.0176) and "effort" (p<0.0001) dimensions, showed a negative attitude change, while the positive attitude change was for "cognitive competence" (p=0.0470) Bioesand "personal assessment" (p=0.0207). In the "cognitive" dimension the average was significantly higher for men (p=0.035) and in the "affective" dimension it was significantly higher for women (p=0.019). The perception for “aptitude for mathematics” decreased significantly at the end of the course (p=0.0001) The stress generated by Biostatistics was medium in 46.51% of the sample. Conclusions: The students appreciated the Biostatistics module, considered it a useful tool, both for personal and professional use. With regard to their initially believed, the difficulty encountered was less, so their stress and effort were less, but they considered that they lacked aptitude for mathematics. Therefore, questionnaires that measure attitude could be a useful tool to redirect teaching strategies and promote a positive attitude towards the discipline.